2013
DOI: 10.1634/theoncologist.2012-0286
|View full text |Cite
|
Sign up to set email alerts
|

Induction Chemotherapy for Locoregionally Advanced Head and Neck Cancer: Past, Present, Future?

Abstract: The treatment of patients with locoregionally advanced squamous cell cancer of the head and neck is still evolving. Induction chemotherapy (IC) is widely used in this patient population and it is unclear how to best incorporate IC into multimodality treatment. Recently, the results of two randomized clinical trials were presented (the PARADIGM and Docetaxel Based Chemotherapy Plus or Minus Induction Chemotherapy to Decrease Events in Head and Neck Cancer trials), which showed no demonstrable benefit of IC foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
0
20
0
3
Order By: Relevance
“…Recently, the results of two randomized clinical trials have been presented (PARADIGM [22] and De-CIDE [23]); induction chemotherapy followed by concurrent chemo-radiation failed to demonstrate a local control benefit over concurrent chemo-radiotherapy alone. However, a lower rate of distant metastatic disease was noted, suggesting that patients who are at high risk for metastatic disease might benefit from induction chemotherapy [24]. The introduction of aggressive high-dose radio-chemotherapy improved disease control at expense of higher rates of treatment-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the results of two randomized clinical trials have been presented (PARADIGM [22] and De-CIDE [23]); induction chemotherapy followed by concurrent chemo-radiation failed to demonstrate a local control benefit over concurrent chemo-radiotherapy alone. However, a lower rate of distant metastatic disease was noted, suggesting that patients who are at high risk for metastatic disease might benefit from induction chemotherapy [24]. The introduction of aggressive high-dose radio-chemotherapy improved disease control at expense of higher rates of treatment-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of taxanes to the cisplatin and 5-fluorouracil induction regimen (TPF) has significantly improved outcomes in comparison with cisplatin and 5-fluorouracil (PF) alone [2,3]. However, as a recent phase II trial (DeCIDE) and a phase III trial (PARADIGM) may have been underpowered to show a survival advantage for TPF induction followed by chemoradiotherapy versus chemoradiotherapy alone [4,5], there is an ongoing debate which subset of patients may benefit from TPF [6,7]. Recently, it has been shown that growth differentiation factor 15 (GDF15) expression can be used as a prognostic biomarker for oral squamous cell carcinoma, and as a predictive biomarker for benefitting from TPF IC [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, a lower rate of distant metastatic disease was noted in the above mentioned DeCIDE study, suggesting that patients who are at high risk for metastatic disease may benefit from IC [7]. For epithelial malignancies, the epithelial-mesenchymal transition (EMT) is considered to be the crucial event in the metastatic process [11].…”
Section: Introductionmentioning
confidence: 99%
“…Su tratamiento puede incluir cirugía, radioterapia y quimioterapia en distintas combinaciones. A pesar del avance en técnicas de tratamiento la sobrevida en estadios avanzados no se ha modificado significativamente en los últimos 20 años 2 . La comprensión de los fenómenos celulares que determinan la aparición de estos tumores podría ser la oportunidad de desarrollar nuevas estrategias terapéuticas.…”
Section: Introduccionunclassified